Kontribusi Mahasiswa KKN STAIN Madina Terhadap Pendidikan dan Keagamaan di Desa Gunung Baringin - Efnijan Nurjannah; Taslimur Rosyady; Suci Nopida; Aminah Nasution; Amas Muda Hasibuan; Mukmin Harianja; Syafitri Daulay; Abdullah Sani; Nur Satia Ritonga; Pitri Hamidah (Jurnal Informasi Pengabdian Masyarakat, 2024)
This service was carried out to reveal the contribution of KKN students from the Mandailing Natal Islamic College to education and religion in Gunung Baringin Village, Portibi District, North Padang Lawas Regency. Education is one of the most important activities in life, as is the case with religion. With these two things, a person can know the purpose of his life. Where education and religion are very closely related, religion is even the most important foundation in education. The science of education based on religion means that religion is the motivation for compiling knowledge, educational concepts and implementing education. From the data obtained, education in Gunung Baringin Village is very diverse or the same as education in the city, only the educational facilities and infrastructure in Gunung Baringin Village are still relatively minimal, this can be seen in the rooms which are still divided into two rooms to fit two. class in one room. Meanwhile, religious activities in Gunung Baringin Village are still lacking, this is because there is very little public awareness so that when there are religious activities such as: congregational prayers, reciting the Yasin Koran every Friday, and the Taqlim Assembly every Saturday, the number of people who come is around 15 people. So, we, STAIN MADINA KKN students, took the initiative to contribute to inviting the community by starting to take part in implementing the activities mentioned above so that the community is also interested in taking part in the activities